Sex-Specific Patterns of Body Mass Index Relationship with White Matter Connectivity. - Rahmani, Farzaneh; Wang, Qing; McKay, Nicole S; Keefe, Sarah; Hantler, Nancy; Hornbeck, Russ; Wang, Yong; Hassenstab, Jason; Schindler, Suzanne; Xiong, Chengjie; Morris, John C; Benzinger, Tammie L S; et al. (J Alzheimers Dis, 2022)
BACKGROUND: Obesity is an increasingly recognized modifiable risk factor for Alzheimer's disease (AD). Increased body mass index (BMI) is related to distinct changes in white matter (WM) fiber density and connectivity. OBJECTIVE: We investigated whether sex differentially affects the relationship between BMI and WM structural connectivity. METHODS: A cross-sectional sample of 231 cognitively normal participants were enrolled from the Knight Alzheimer Disease Research Center. Connectome analyses were done with diffusion data reconstructed using q-space diffeomorphic reconstruction to obtain the spin distribution function and tracts were selected using a deterministic fiber tracking algorithm. RESULTS: We identified an inverse relationship between higher BMI and lower connectivity in the associational fibers of the temporal lobe in overweight and obese men. Normal to overweight women showed a significant positive association between BMI and connectivity in a wide array of WM fibers, an association that reversed in obese and morbidly obese women. Interaction analyses revealed that with increasing BMI, women showed higher WM connectivity in the bilateral frontoparietal and parahippocampal parts of the cingulum, while men showed lower connectivity in right sided corticostriatal and corticopontine tracts. Subgroup analyses demonstrated comparable results in participants with and without positron emission tomography or cerebrospinal fluid evidence of brain amyloidosis, indicating that the relationship between BMI and structural connectivity in men and women is independent of AD biomarker status. CONCLUSION: BMI influences structural connectivity of WM differently in men and women across BMI categories and this relationship does not vary as a function of preclinical AD.

Chinese Herbal Medicine for Vascular Dementia: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials. - Xu, Qing-Qing; Shan, Chun-Shuo; Wang, Yong; Shi, Yi-Hua; Zhang, Qi-Hao; Zheng, Guo-Qing (J Alzheimers Dis, 2018)
BACKGROUND: Vascular dementia (VaD) is the second common form of dementia and Chinese herbal medicine (CHM) has been used for aging-related disorders for thousands of years. However, there is still a lack of scientific evidence using CHM for VaD. OBJECTIVE: To conduct a systematic review to assess the current evidence available for the effectiveness and safety of CHM for VaD. METHODS: Six databases were searched for high-quality randomized-controlled clinical trials that met the requirements of at least 4 of the 7 domains of the Cochrane risk of bias tool from their inception to February 2017. RevMan 5.3 was applied for data analysis. RESULTS: Forty studies with 42 comparisons and 3,572 individuals were included. The studies investigated the CHM versus placebo (n = 4), CHM versus western conventional treatment (WCT) (n = 36), and CHM plus WCT versus WCT (n = 2). Meta-analysis showed that CHM for VaD could improve Mini-Mental State Examination (MMSE), the Activities of Daily Living, Hasegawa's dementia scale, and clinical effective rate but had statistically similar effect based on Blessed Behavior Scale (BBS) outcome when compared with WCTs. When compared with placebo, CHMs were more beneficial in improving MMSE but showed no significant difference in BBS scores. CHM as adjuvant therapy exerted an additive anti-VaD benefit on MMSE scores. The participants of CHM group had fewer adverse events than that of the placebo group or WCT group. CONCLUSION: The findings of the present study support, at least to an extent, that CHM can be recommended for routine use for treatment of VaD.

Urine-Based Biomarkers for Alzheimer's Disease Identified Through Coupling Computational and Experimental Methods. - Yao, Fang; Hong, Xiaoyu; Li, Shuiming; Zhang, Yan; Zhao, Qing; Du, Wei; Wang, Yong; Ni, Jiazuan (J Alzheimers Dis, 2018)
Alzheimer's disease (AD) is a chronic neurodegenerative disorder contributing to nearly 70% of dementia cases. However, no diagnostic protein biomarkers are available in urine. In this study, we combined computational and experimental methods to identify urinary biomarkers for AD. First, by analyzing brain tissue-based gene expression data of AD, 2,754 differentially expressed genes were identified, 559 of which were predicted to encode urine-excretory proteins that might act as candidate protein biomarkers of AD. GO enrichment analyses implied that they were mainly involved in microtubule-based process, myelin sheath, and calcium ion binding, suggesting that they might be associated with AD pathogenesis. In order to verify these proteins in urine, an iTRAQ experiment was carried out to analyze urine samples from AD patients and healthy controls, and 15 proteins were detected. Based on the expression changes of these proteins, 4 proteins were chosen for further validation by ELISA experiment, and SPP1, GSN, and IGFBP7 were found to be differentially expressed in the urine of AD patients. After a literature survey, we found that they were involved in AD pathophysiology and might serve as new urine biomarkers for AD. To our knowledge, this is the first time that urine biomarkers for AD were identified by combining computational and experimental methods. Furthermore, this is the first time SPP1, GSN, and IGFBP7 have been reported as potential urine protein biomarkers for AD. Therefore, our findings might provide significant guidance for finding early biomarkers of AD in urine.

Mitochondrial Repair Effects of Oxygen Treatment on Alzheimer's Disease Model Mice Revealed by Quantitative Proteomics. - Wang, Hao; Hong, Xiaoyu; Wang, Yong (J Alzheimers Dis, 2017)
Mitochondrial dysfunction plays a pivotal role in Alzheimer's disease (AD), even before signs of AD pathology are evident. Our previous research has shown that oxygen treatment can improve cognitive function in AD model mice. To address whether oxygen treatment is beneficial to mitochondrial biology, we analyzed differential expressions of hippocampal mitochondrial proteins in AD model mice given supplementary oxygen. Numerous respiratory chain, Kreb's cycle, and glycolysis proteins were upregulated significantly after oxygen treatment, suggesting that oxygen therapy can alleviate mitochondrial damage. Furthermore, the treatment was associated with decreased expressions of some AD biomarkers, suggesting oxygen treatment to be a potential therapy for AD.

Proteomics Analysis of Blood Serums from Alzheimer's Disease Patients Using iTRAQ Labeling Technology. - Shen, Liming; Liao, Liping; Chen, Cheng; Guo, Yi; Song, Dalin; Wang, Yong; Chen, Youjiao; Zhang, Kaoyuan; Ying, Ming; Li, Shuiming; Liu, Qiong; Ni, Jiazuan (J Alzheimers Dis, 2017)
Alzheimer' disease (AD) is the most common form of dementia affecting up to 6% of the population over the age of 65. In order to discover differentially expressed proteins that might serve as potential biomarkers, the serums from AD patients and healthy controls were compared and analyzed using the proteomics approach of isobaric tagging for relative and absolute quantitation (iTRAQ). For the first time, AD biomarkers in serums are investigated in the Han Chinese population using iTRAQ labeled proteomics strategy. Twenty-two differentially expressed proteins were identified and out of which nine proteins were further validated with more sample test. Another three proteins that have been reported in the literature to be potentially associated with AD were also investigated for alteration in expression level. Functions of those proteins were mainly related to the following processes: amyloid-β (Aβ) metabolism, cholesterol transport, complement and coagulation cascades, immune response, inflammation, hemostasis, hyaluronan metabolism, and oxidative stress. These results support current views on the molecular mechanism of AD. For the first time, differential expression of zinc-alpha-2-glycoprotein (AZGP1), fibulin-1 (FBLN1), platelet basic protein (PPBP), thrombospondin-1 (THBS1), S100 calcium-binding protein A8 (S100A8), and S100 calcium-binding protein A9 (S100A9) were detected in the serums of AD patients compared with healthy controls. These proteins might play a role in AD pathophysiology and serve as potential biomarkers for AD diagnosis. Specifically, our results strengthened the crucial role of Aβ metabolism and blood coagulation in AD pathogenesis and proteins related to these two processes may be used as peripheral blood biomarkers for AD.

Quantitative Proteomics Reveals the Mechanism of Oxygen Treatment on Lenses of Alzheimer's Disease Model Mice. - Wang, Hao; Wang, Ying; Hong, Xiaoyu; Li, Shuiming; Wang, Yong (J Alzheimers Dis, 2016)
BACKGROUND: Alzheimer's disease (AD) is a neurodegenerative disease with well-characterized pathological features. Yet the underlying mechanisms have not been resolved and an effective therapeutic approach is lacking. Cerebral hypoxia is considered a risk factor of AD. OBJECTIVE: We tested whether oxygen supplementation can relieve AD symptoms and how it affects the expression levels of proteins in the lens. METHODS: Triple transgenic AD model (3xTg-AD) mice were divided into oxygen treated (OT) and control (Ctrl) groups. Their cognitive performances were tested in a Morris water maze (MWM) paradigm. Then, their eye lens tissues were subjected to quantitative proteomics analysis by the iTRAQ (isobaric tags for relative and absolute quantification) method. The up- and downregulated proteins were classified according to a Gene Ontology (GO) database in PANTHER. Behavioral and proteomic data were compared between the groups. RESULTS: Mice in the OT group had better learning and memorizing performance compared with the Ctrl group in MWM test. Lenses from the OT group had 205 differentially regulated proteins, relative to lenses from the Ctrl group, including proteins that are involved in the clearance of amyloid β-protein. CONCLUSION: The results of this study indicate that oxygen treatment can improve cognitive function in AD model mice and alters protein expression in a manner consistent with improved redox regulation.